(untitled) (Nepalese Veterinary Journal, 2018)
This study was carried out to identify the effects of season and semen extender ratio on hatchability of artificially inseminated turkeys of Chitwan, Nepal. Trials were conducted using four treatments of different dilutions of semen with skim milk powder in the ratio of 1:1 (T1), 1:2 (T2), 2:3 (T3) and 3:4 (T4). The 32 turkeys were artificially inseminated in 4 days interval for 3 months. The dose of insemination was 0.03 ml and insemination were done around 6:00 p.m. Trials were done in winter and spring seasons of 2017 to find out the seasonal variation on hatchability of turkey. The data were analyzed using GenStat3.6.2, computer software. The hatchability was noted on total eggs as well as fertile eggs. In total eggs, it was found that hens with T1 (67.80%) gave higher hatchability than T2 (63.82%), T3 (63.04%) and T4 (63.98%) whereas in fertile eggs, T3 (83.26%) and T4 (83.01%) gave higher hatchability than T1 (82.96%) and T2 (82.90%). Hatchability rate was almost similar in both spring and winter seasons in total eggs with non-significant differences. On the other hand, in fertile eggs, the hatchability rate was found higher in spring season. Similarly, seasonal effect on hatchability rate of various semen extender ratios in total eggs and fertile eggs was also carried out. In total eggs, T1 and T3 produced higher hatchability rate in spring than in winter; T2 had similar hatchability rate in both seasons and T4 had higher hatchability in winter than in spring. However, there were no significant differences on hatchability rate of semen extender ratio due to seasonal variation. In fertile eggs, all the 4 dilutions had more hatchability rate in winter season than in spring with significance (P<0.05). The hatchability was highest in T1 (85.19%) in winter season. The present study provides evidence that in total eggs of turkey inseminated with 1:1 semen dilutions provides more hatchability rate than other dilutions, whereas fertile eggs have more hatchability with dilutions 1:2 and 2:3 than others and hatchability rate based on total eggs is higher in spring than winter.